2008
DOI: 10.1021/cr078003i
|View full text |Cite
|
Sign up to set email alerts
|

Complexation and Separation of Lanthanides(III) and Actinides(III) by Heterocyclic N-Donors in Solutions

Abstract: 1. Introduction 4208 2. Properties of N-Donors in Solutions 4210 2.1. Basicity 4210 2.1.1. Data on the Protonation of Selected N-Donors 4210 2.2. Protonation in an Organic Solvent 4210 2.3. Protonation of N-Donors in Aqueous Systems 4212 2.3.1. Terpy and Its Derivatives 4212 2.3.2. TPTZ and DMTP 4214 2.3.3. Pyridyl-Substituted Alkaneamines 4214 2.4. Solubility and Distribution between Two Liquid Phases 4214 2.5. Self-Association 4215 2.6. Configuration 4215 2.6.1. Terpy 4215 2.6.2. Other Ligands 4215 2.7. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
371
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(378 citation statements)
references
References 124 publications
6
371
1
Order By: Relevance
“…Few years ago, it was discovered that nitrogen ligands are able to exhibit a selectivity between An and Ln [184]. Therefore, the researches were focused on the chemistry of polyazine extractants [185]. The design of extractant ligands for lanthanide/actinide separation exploits the possibility of a significant covalency in the 5f series.…”
Section: Assessing Covalency In Nitrogen Ligand-actinide Complexesmentioning
confidence: 99%
“…Few years ago, it was discovered that nitrogen ligands are able to exhibit a selectivity between An and Ln [184]. Therefore, the researches were focused on the chemistry of polyazine extractants [185]. The design of extractant ligands for lanthanide/actinide separation exploits the possibility of a significant covalency in the 5f series.…”
Section: Assessing Covalency In Nitrogen Ligand-actinide Complexesmentioning
confidence: 99%
“…The -lines at 59.5 keV, and 121.8 keV were examined for 241 Am, and 152 Eu, respectively. The acidities of the initial and final aqueous solutions were 90 determined by potentiometric titration against sodium hydroxide solution (0.1 mol dm −3 ) using a Metrohm 751 GPD Titrino device. The distribution ratio D was measured as the ratio between the radioactivity in the organic and the aqueous phase.…”
Section: Solvent Extraction Studiesmentioning
confidence: 99%
“…Heterocyclic compounds containing soft donor atoms are capable of separating two groups of elements. For example, it has been reported that ligands containing aromatic N atoms as donor atoms coordinate An(III) more strongly than Ln(III), due to a greater covalent character of the An(III)-N bond [1][2][3]. As a continuation of our structural study on 6,6′-bis(substituted)-5,5′-bi-1,2,4-triazines as potential Nheterocyclic ligands for the extraction of nuclear waste [4], we describe in this paper the crystal structure of 3,3′-di(furan-2-yl)-5,5′-bi-1,2,4-triazine.…”
Section: Discussionmentioning
confidence: 99%